Pengembangan Algoritma Hybrid Flowshop Three-Stage Dengan Mempertimbangkan Waktu Setup - Dana Marsetiya Utama; Annisa Kesy Garside; Wahyu Wicaksono (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2019)
Hybrid flow shop scheduling is one topic that is often reviewed by researchers at this time. Hybrid flow shop scheduling is the development of problems from pure flow shop. Flow shop problems have one machine at each stage. In this problem, each stage of operation has a machine that is arranged in parallel. This article aims to discuss the issue of hybrid flow shop scheduling at three stage to minimize makespan. Some previous studies discussed scheduling problems by considering setup time. However, such research is generally for the problem of pure flow shop. Therefore, a new algorithm is proposed to solve the problem. The proposed algorithm is developed from the Pour heuristic algorithm. Several experiments were conducted to determine the performance of the proposed algorithm. This study uses ten numerical experiments. This experiment uses the number of jobs varying from 5 jobs to 50 jobs. The results of numerical experiments show that the proposed algorithm has better performance compared to some other algorithms. The proposed method produces an effective solution if it is used to solve problems with a large number of jobs..